2013
DOI: 10.1073/pnas.1311261110
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight on the recognition of surface-bound opsonins by the integrin I domain of complement receptor 3

Abstract: Complement receptors (CRs), expressed notably on myeloid and lymphoid cells, play an essential function in the elimination of complement-opsonized pathogens and apoptotic/necrotic cells. In addition, these receptors are crucial for the cross-talk between the innate and adaptive branches of the immune system. CR3 (also known as Mac-1, integrin α M β 2 , or CD11b/CD18) is expressed on all macrophages and recognizes iC3b on complement-opsonized objects, enabling their phagocytosis. We demonstrate that the C3d moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
197
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(218 citation statements)
references
References 52 publications
(55 reference statements)
19
197
2
Order By: Relevance
“…We also identified an anti-C3d mAb that impaired binding of CR3-a M I considerably ( Figure 1F). Although avidity during cell-cell interactions may influence the binding profile, and additional contacts with CR3 may be involved in the case of iC3b, 8 our study demonstrates that C3dg can act as independent binding partner for CR3.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…We also identified an anti-C3d mAb that impaired binding of CR3-a M I considerably ( Figure 1F). Although avidity during cell-cell interactions may influence the binding profile, and additional contacts with CR3 may be involved in the case of iC3b, 8 our study demonstrates that C3dg can act as independent binding partner for CR3.…”
Section: Resultsmentioning
confidence: 71%
“…7 Recently, structural studies revealed that the C3d domain contains the interaction site of iC3b for CR3. 8 We therefore hypothesized that C3dg may act as independent opsonin that contributes to erythrophagocytosis, thereby corroborating the mechanism of extravascular hemolysis in PNH.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…CR1 (CD35) is both a complement receptor for C3b, iC3b and C4b and a complement inhibitor, by competing with factor B (FB) for C3b binding and by functioning as a co-factor for factor I (FI) [6]. CR2 (CD21) binds iC3b, and especially C3d/C3dg, CR3 (MAC-1, CD11b/CD18) binds iC3b and C3d/C3dg, whereas CR4 (gp150/95, CD11c/CD18) binds only iC3b [7][8][9][10][11][12]. Another complement receptor, complement receptor of the immunoglobulin superfamily (CRIg), binds to C3b and iC3b and also to soluble C3c [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ultrasound responsive systems, it is required for the stabilization of acoustic cavitation's gas-liquid interface and the compatibility with liquid interface to generate gas bubbles. The primary requirements of the stabilized system are extended circulation lifetime, effective size range, and efficient stimulated release of encapsulated drug via the application of ultrasound [67][68].…”
Section: Ultrasound-sensitive Drug Deliverymentioning
confidence: 99%